SPIRITUAL LEADERSHIP AND COMMITMENT ORGANIZATIONAL WITH THE MEDIATION WORK SATISFACTION AMONG ISLAMIC TEACHERS - Muhammad Fajrul Islam F; Armanu; Suryadi, Nanang (International Journal of Economic, Business, Accounting, Agriculture Management and Sharia Administration (IJEBAS), 2023)
This study aims to examine the effect of spiritual leadership on the organizational commitment of Islamic school teachers in South Sulawesi and the mediating role of work satisfaction in these two variables. The data were obtained by distributing questionnaires to 144 teachers. The data analysis used was Structural Equation Modeling (SEM). The results showed that spiritual leadership has no effect on the organizational commitment of Islamic school teachers but will be helped if supported by work satisfaction as a mediator. Furthermore, spiritual leadership has a significant relationship with teachers' work satisfaction, and work satisfaction has a significant effect on teachers' organizational commitment. The results of the work satisfaction mediation test perfectly mediated the effect of spiritual leadership on the organizational commitment of Islamic school teachers. Spiritual leadership must be supported by work satisfaction to increase organizational commitment among teachers. Islamic educational institutions in South Sulawesi must improve spiritual leadership patterns and maintain work satisfaction in order to increase teacher commitment to the organization.